2016
DOI: 10.3390/su8070677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use and Cover Change on Air Quality in Urban Sprawl

Abstract: Due to the frequent urban air pollution episodes worldwide recently, decision-makers and government agencies are struggling for sustainable strategies to optimize urban land use/cover change (LUCC) and improve the air quality. This study, thus, aims to identify the underlying relationships between PM 10 concentration variations and LUCC based on the simulated PM 10 surfaces in 2006 and 2013 in the Changsha-Zhuzhou-Xiangtan agglomeration (CZT), using a regression modeling approach. LUCC variables and associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…According to the previous LUR research findings on the selection of geographical feature characteristics [14,[29][30][31], data collected for LUR modelling in this study contains annual average PM2.5 concentrations, elevation, AOD, climate characteristics (temperature, wind speed, relative humidity, atmospheric pressure, and precipitation), road traffic, land use and cover, industrial plants, and surface dust. The distribution of PM2.5 monitoring sites and the partial basic geographical feature data, within the BTH region during the study period of 1 January 2015 to 31 December 2015, are shown in Figure 1.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
“…According to the previous LUR research findings on the selection of geographical feature characteristics [14,[29][30][31], data collected for LUR modelling in this study contains annual average PM2.5 concentrations, elevation, AOD, climate characteristics (temperature, wind speed, relative humidity, atmospheric pressure, and precipitation), road traffic, land use and cover, industrial plants, and surface dust. The distribution of PM2.5 monitoring sites and the partial basic geographical feature data, within the BTH region during the study period of 1 January 2015 to 31 December 2015, are shown in Figure 1.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
“…Therefore, it is important to ensure the quality and evaluate the performance of the C6.1 AOD products for China. Furthermore, the properties of aerosol are known to be correlated to surface types (Wei et al, 2017;Zou et al, 2016) and geographical conditions (He et al, 2016;Li et al, 2003;Wang et al, 2010) in China. In the past, many scholars have undertaken excellent research to evaluate the AOD products for China (He et al, 2010(He et al, , 2017Tao et al, 2015;Wang et al, 2010;Wei et al, 2017;Xie et al, 2011), yet no one has simultaneously considered the specific land cover types and the digital elevation model (DEM).…”
Section: Introductionmentioning
confidence: 99%
“…To account for the regional variation of air quality, many researchers have examined the influencing factors relevant to urban air quality. In these studies, factors as meteorological elements, land use and land cover change, urbanization, industrialization, energy structure, and transport patterns have been reported to have significant impact on urban air quality (Krummel et al, 1984;Shaw et al, 2010;Tai et al, 2010;Zhang and Fan, 2011;Guan et al, 2014;Lu and Han, 2014;Patton et al, 2014;Li et al, 2015;Lin and Wang, 2016;Qin and Liao, 2016;Sun et al, 2016;Zou et al, 2016;Hu et al, 2017;Yan et al, 2017). The previous studies, in general, have predominantly observed the characteristics of determinants within a single region or among different cities.…”
Section: Introductionmentioning
confidence: 99%